(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Formulaic sequences and discourse markers are consistently used in academic writing. This study offers a new dimension to the study of formulaic sequences in academic discourses, focusing mainly on the views of key stakeholders in academic writing, including university lecturers, non-academic staff of universities who are also academic writers, independent writers and journal editors. A total of 375 respondents were engaged in the study across the different stakeholders group. Data was collected with questionnaire, and analysis was done using relevant statistical tools. The study reveals that over 73% of the academic writing stakeholders accepted that formulaic sequences and discourse markers have become an indispensable component of academic writing. Also, over 53% of the academic stakeholders who rejected the claim that writers unconsciously deploy formulaic sequences and discourse markers in their studies. The result further indicates that almost 70% of the respondents accepted that the use of formulaic sequences has constrained writers in academic domain from being free in their choice of linguistic features in different contexts.in other words, although the writers are consciously making use these formulaic sequences ad discourse markers, they are constrained to use them in relation to the context and semantics of the discourse. The findings also shows that over 78% affirm that writers chose certain formulaic sequences to suit their discourse without paying close attention to the functions, but the context determines the functions of these tools. Finally, over 87% of the academic writing stakeholders generally accepted that academic writers also deploy discourse markers and formulaic sequences to create cohesion, embed style, avoid repetition and create contextual effects. It is thus concluded that formulaic sequences and discourse markers remain vital for academic writing, and writers and editors need to exert clear understanding of their usage in relation to context and discourse effects.